Kindergarten Curriculum Revolution: Aligning the Independent Curriculum with the Needs of the Global Education Industry - Fitria, Ulfa; Muhammad Imam Khaudli (Journal of Basic Education Research, 2025)
Purpose of the study: This study aims to examine how the Merdeka Curriculum is implemented at TK Darussalam Blokagung Banyuwangi and to identify the challenges and strategies in aligning this independent curriculum with global education demands, as well as to propose practical recommendations for enhancing its implementation Methodology: Employing a descriptive qualitative case study approach, the research involved one principal and six homeroom teachers, with data gathered through structured observations, semi-structured interviews, and documentation of classroom activities; a comprehensive literature review informed the analysis, which was conducted using manual transcript analysis Main Findings: Findings reveal that the Merdeka Curriculum enables flexible lesson planning that fosters religious character, independence, creativity, and collaboration, leading to heightened student enthusiasm and engagement; however, implementation barriers—such as limited teacher proficiency in project-based learning, inadequate facilities, and insufficient parental involvement—were evident, prompting the school to conduct regular professional development and strengthen community partnerships to improve curriculum delivery Novelty/Originality of this study: Uniquely, this study focuses on a rural PAUD setting, offering novel insights into adapting independent curriculum frameworks to meet global education industry requirements in under-resourced contexts and generating context-specific recommendations that advance current understanding of curriculum flexibility and the integration of local and global educational values